Stereotaxis: Its history, generalities and updating. - José Ramón Tejera del Valle; Juan Francisco Piñeiro Martí; Osmany Morales Sabina (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2005)
The brain is considered the human being's organ rector, it is characterized by its fragility, complexity and fineness, therefore any surgical intervention on him should be precise and sure. The present publication revises in way chronological aspects of national and international relevance related with the history of the stereotaxy, the medicals principles and technicians in that its operation is sustained approaches, and it summarizes the indications, complication and contraindications of the technique. The work conception is explained in team that they require these considerations, based on the experience of Service of Neurosurgery of Cienfuegos, current considerations of the present and future of the stereotaxy are emitted.